O uso de tintas especiais em embalagens para bebidas como estratégia de marketing - Ferreira, Meryen Gonçalves (2013)
Through exploratory research, relevant data were collected on the currentbeverage industry in Brazil, labeling, printing systems, special inks, consumer behavior and gathered examples of packaging for beverages using special inks and print marketing strategy. From this information, we analyzed key points of the packages presented.